2021
DOI: 10.1021/acs.nanolett.1c04288
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Ultimate Efficiency of Solar Energy Harvesting with a Nonreciprocal Multijunction Solar Cell

Abstract: The Landsberg limit represents the ultimate efficiency limit of solar energy harvesting. Reaching this limit requires the use of nonreciprocal elements. The existing device configurations for attaining the Landsberg limit, however, are very complicated. Here, we introduce the concept of a nonreciprocal multijunction solar cell and show that such a cell can reach the Landsberg limit in the idealized situation where an infinite number of layers are used. We also show that such a nonreciprocal multijunction cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…In this study, we use a degenerately doped magneto-optical semiconductor paired with a GMR coupled to free-space incident radiation to demonstrate nonreciprocal absorption in the IR regime when a moderate magnetic field ( B up to 1.2 T) bias is applied. The degree of reciprocity breaking is largest at narrower incidence angles θ i (45° to 55°), making the design potentially useful for cascading multiple emitters/absorbers to achieve directional flow of energy ( 39 ). The methods used to model, design, and fabricate the structure presented in this manuscript can be used for future implementations of nonreciprocal absorbers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use a degenerately doped magneto-optical semiconductor paired with a GMR coupled to free-space incident radiation to demonstrate nonreciprocal absorption in the IR regime when a moderate magnetic field ( B up to 1.2 T) bias is applied. The degree of reciprocity breaking is largest at narrower incidence angles θ i (45° to 55°), making the design potentially useful for cascading multiple emitters/absorbers to achieve directional flow of energy ( 39 ). The methods used to model, design, and fabricate the structure presented in this manuscript can be used for future implementations of nonreciprocal absorbers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the voltages of the layers on the hot side are nonpositive, we start by setting V H (0) = 0, and we will later show that this choice is consistent from a power optimization point of view. Under this condition, finding V L ( E ) as a function of E that maximizes the cold side power is identical to the procedure introduced by Park et al, where efficiency-maximizing condition of a nonreciprocal infinite-junction solar cell is determined . This leads to the following result: V normalL ( E ) = E q ( 1 T L T H ) W normalL = σ ( T H 4 4 3 T H 3 T L + 1 3 T L 4 ) where q is the elementary charge, σ is the Stefan–Boltzmann constant, and W L is the total power output from the cold side PV layers.…”
Section: Nonreciprocal Tpv Systemmentioning
confidence: 99%
“…Our work is related to ref , which showed that in solar energy harvesting the Landsberg limit can be reached by a multilayered nonreciprocal PV cell. Compared with the ref , here we place the PV cells on both the hot and the cold side of the heat engine, as is appropriate for a TPV system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most promising renewable and nonpolluting energy sources for future energy supply, the conversion and utilization of solar energy are of great importance. , The utilization of solar energy includes several common approaches such as light utilization, solar photochemical utilization, and so on. Both processes comprise electron–hole (e–h) pair recombination.…”
mentioning
confidence: 99%